Exploration of Guest Preferences toward Quality of Hotel Staff Service - Ayu Irmma Trisania Pramesti; Anak Agung Ayu Sri Maharani; Adinda Prasetya Yulianti; Ai Rainaya Cahyani; Annisa Larasati Anggreni; Ayu Ulan Permatasari; Ni Desak Made Santi Diwyarthi (Westscience Press, 2024)
This study explores guests' preferences regarding the quality of service provided by hotel employees, particularly those in the accounting department of SI Hotel in Denpasar. The research was conducted using a qualitative method, involving in-depth interviews with five individuals who visited SI Hotel. The results were deterioration in service standards among staff working in the accounting division of hospitality businesses comprises an incapacity to address customer grievances, tardiness in completing tasks, inaccuracies in calculations or reporting, negligence towards protocols, inconsistent attendance, and resistance to adaptation to change. To enhance service excellence within the accounting department of SI Hotel, management should consider implementing measures such as training sessions, constructive feedback mechanisms, fostering employee engagement, offering incentives, and promoting work-life balance initiatives.